The Correlation between Service Quality of Maternal and Child Healthcare/Family Planning Clinic and Degree of Maternal and Child Health at Two Primary Health Care Centers in Jember - Kunthi Kencana Makayasa Putri; Ida Srisurani Wiji Astuti; Sugiyanta Sugiyanta (Faculty of Medicine, University of Jember, 2016)
The high Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR) is still a major health problem in Indonesia. As an one of indicator to assess the quality of maternal and child healthcare is MMR and IMR. Service quality consists of five dimensions i.e., tangible, responsiveness, reliability, assurance, and empathy. The aim of this research was to determine the correlation between service quality of maternal and child healthcare/family planning polyclinic and degree of maternal and child health at Two Primary Health Care Centers in Jember. This research used cross-sectional design with 144 respondents. Service quality was measured using ServQual questionnaire and degree of maternal and children health were measured using MMR and IMR. The results of statistical test with Spearman correlation test showed that the significance (p) = 0.000 and correlation coefficients (r) = 0.690. Thus, it can be concluded that there were a strong correlation between service quality of maternal and child healthcare/family planning clinic and degree of maternal and child health at Two Primary Health Care Centers in Jember. Keywords: Maternal Mortality Rate, Infant Mortality Rate, ServQual.